Broadband light trapping in thin film solar cells with self-organized plasmonic nano-colloids. (11th March 2015) - Mendes, Manuel J.; Morawiec, Seweryn; Mateus, Tiago; Lyubchyk, Andriy; Águas, Hugo; Ferreira, Isabel; Fortunato, Elvira; Martins, Rodrigo; Priolo, Francesco; Crupi, Isodiana
Abstract: The intense light scattered from metal nanoparticles sustaining surface plasmons makes them attractive for light trapping in photovoltaic applications. However, a strong resonant response from nanoparticle ensembles can only be obtained if the particles have monodisperse physical properties. Presently, the chemical synthesis of colloidal nanoparticles is the method that produces the highest monodispersion in geometry and material quality, with the added benefits of being low-temperature, low-cost, easily scalable and of allowing control of the surface coverage of the deposited particles. In this paper, novel plasmonic back-reflector structures were developed using spherical gold colloids with appropriate dimensions for pronounced far-field scattering. The plasmonic back reflectors are incorporated in the rear contact of thin film n-i-p nanocrystalline silicon solar cells to boost their photocurrent generation via optical path length enhancement inside the silicon layer. The quantum efficiency spectra of the devices revealed a remarkable broadband enhancement, resulting from both light scattering from the metal nanoparticles and improved light incoupling caused by the hemispherical corrugations at the cells' front surface formed from the deposition of material over the spherically shaped colloids.